Pleomorphic Adenoma of The Nasal Septum - Elwany, samy; Mandour, Zeyad; Talaat, Iman (Journal of Otolaryngology Advances, 2014)
Pleomorphic adenomas are uncommon tumors of the nasal cavity. They arise from minor salivary glands, and usually originate from the nasal septum. The tumors are more common in middle-aged females. We present a series of 8 cases of intranasal pleomorphic adenomas. Seven of these tumors originated from the nasal septum, and only one of them originated from the lateral nasal wall. Histopathologic examination of the tumors showed that these tumors have higher epithelial and lower stromal components compared to pleomorphic adenomas of major salivary glands. Endoscopic resection was performed in all cases and the patients were followed up for one year. No recurrences or complications were observed in this series. Endoscopic resection is recommended as the treatment of choice because of its proven efficacy and low morbidity.
Keywords: pleomorphic; adenoma; salivary; nasal; septum